Index modulation aided generalized space-time block coding: A unified MIMO framework - Zhiqin Wang; Hui Liu; Lixia Xiao; Liuke Li; Guochao Song; Tao Jiang (Digital Communications and Networks)
In this paper, Index Modulation (IM) aided Generalized Space-Time Block Coding (GSTBC) is proposed, which intrinsically exploits the benefits of IM concept, diversity gain and spatial multiplexing gain. Specifically, the information bits are partitioned into U groups, with each being modulated by IM symbols (i.e. Spatial Modulation (SM), Quadrature SM (QSM),etc). Next, the structure of GSTBC is invoked for each K IM symbol, and a total of μ ​= ​U/K GSTBC codes are transmitted via T time slots. A Block Expectation Propagation (B-EP) detector is designed for the proposed IM-GSTBC structure. Moreover, the theoretical Average Bit Error Probability (ABEP) is derived for our IM-GSTBC system, which is confirmed by the simulation results and helpful for performance evaluation. Simulation results show that our proposed IM-GSTBC system is capable of striking an efficient trade-off between spatial multiplexing gain, spatial diversity gain as well as implementation cost imposed for both small-scale and large-scale MIMO antenna configurations.